Macrophage regulated cell death: implications and mechanisms in organ transplantation - Hou, Jincheng; Li, Chenghao; Li, Geng; Yim, Wai Yen; Geng, Bingchuan; Cheng, Yuqi; Wang, Zihao; Fan, Zhengfeng; Tong, Fuqiang; Shi, Jiawei; Wang, Yixuan; Dong, Nianguo (Frontiers in Immunology, 2025)
Organ transplantation is a critical treatment for end-stage organ failure, but long-term graft survival remains suboptimal due to ischemia-reperfusion injury (IRI) and transplant rejection. The immune microenvironment, especially macrophages, plays a key role in these processes. Various forms of regulated cell death (apoptosis, autophagy, pyroptosis, ferroptosis, necroptosis) in macrophages significantly influence transplant rejection by mediating cellular communication and shaping the immune microenvironment. Apoptosis, pyroptosis, ferroptosis and necroptosis in macrophages exacerbate graft rejection while autophagy in macrophages protects against transplant rejection by reducing inflammation.This paper reviews the specific molecular mechanisms of macrophage regulated cell death, their impact on the IRI and transplant rejection, thus further provide potential therapeutic target for improving transplant outcomes.